Do exotic pine plantations favour the spread of invasive herbivorous mammals in Patagonia? - Lantschner, María Victoria (2013)
Changes in land use patterns and vegetation can trigger ecological change in occupancy and community composition. Among the potential ecological consequences of land use change is altered susceptibility to occupancy by invasive species. We investigated the responses of three introduced mammals (red deer, Cervus elaphus; wild boar, Sus scrofa; and European hare, Lepus europaeus) to replacement of native vegetation by exotic pine plantations in the Patagonian forest-steppe ecotone using camera-trap surveys (8633 trap-days). We used logistic regression models to relate species presence with habitat variables at stand and landscape scales. Red deer and wild boar used pine plantations significantly more frequently than native vegetation. In contrast, occurrence of European hares did not differ between pine plantations and native vegetation, although hares were recorded more frequently in firebreaks than in plantations or native vegetation. Presence of red deer and wild boar was positively associated with cover of pine plantations at the landscape scale, and negatively associated with mid-storey cover and diversity at the stand scale. European hares preferred sites with low arboreal and mid-storey cover. Our results suggest that pine plantations promote increased abundances of invasive species whose original distributions are associated with woodlands (red deer and wild boar), and could act as source or pathways for invasive species to new areas.